PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN AKTIVITAS DAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SMP NEGERI 3 BATANGHARI - Kurniati, Brigita Ivana; Ahmad, H Jazim; Rahmawati, Dwi (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2019)
This study aims to determine the increase in learning activities and students' critical thinking abilities in circle material through the application of cooperative learning types Examples and Non Examples in Eight Grade Students of SMP Negeri 3 Batanghari. The research method is classroom action research which consists of four stages including: planning, implementation, observation, and reflection. The subjects of this study were students of class Eight Grade Students of SMP Negeri 3 Batanghari. Data collection uses instruments in the form of learning activity observation sheets and critical thinking ability test sheets consisting of 5 questions. The results of the study indicate the existence of: 1) Increased learning activities in the learning process. This can be seen from the increase in each indicator, the average percentage of learning activities per indicator, namely: a) focus of material presentation from teacher in the pre-survey is 78%. It decreases to 69.23% in the first cycle, then increasing to 82% in second cycle. b) Asking questions, in pre-survey at 9%, increased to 46.17% in first cycle, then increased to 62.8% in second cycle. c) Answering questions, in pre-survey by 4%, increasing to 42.33% in first cycle, and then increasing to 61.57% in second cycle. d) The activity in group discussions, in pre-survey by 57%, increasing to 55.1% in the first cycle, and then increasing to 65.37% in cycle II. e) Presenting group assignments, in pre-survey by 22%, increasing to 42.27% in first cycle, and then increasing to 62.8% in second cycle. 2) Increasing the percentage of learning outcomes of students' critical thinking skills from pre-survey by 30.33%, increasing to 30.76% in cycle I, and then increasing to 65.38% in cycle II. The conclusion of this study is that the application of the cooperative learning model type Examples Non Examples can: 1) Increase the learning activities of Eight Grades students of SMP Negeri 3 Batanghari 2018/2019 Academic Year. 2) Learning outcomes that refer to the critical thinking skills of Eight Grade Students of SMP Negeri 3 Batanghari ware improve.